2012
DOI: 10.2355/isijinternational.52.2210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Rate and Ti Addition on the Microstructure and Mechanical Properties in As-cast Condition of Hypereutectic High Chromium Cast Irons

Abstract: The effect of cooling rate and Ti additions on the mechanical properties and carbides characteristics such as morphology, size distribution and composition was studied in high-chromium cast irons containing Fe-17 mass%Cr-4 mass%C. Based on the size distribution, composition and morphology, M7C3 type carbides were roughly classified into "primary M7C3 carbides" and "eutectic M7C3 carbides" with a 11.2 μm border size. Thereafter, the change of the solidification structure and especially the refinement of carbide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Our previous study by Liu, et al, 1) and other studies by Zhi, et al, 2) Chung, et al 3) and Bedolla-Jacuinde, et al 4) have reported the experimental results on Fe-4wt%C-17wt%Cr, Fe-4wt%C-20wt%Cr, Fe-4wt%C-25wt%Cr and Fe-2.5wt%C-16wt%Cr high chromium cast irons with different Ti-additions, as shown in Table 1. They found that, besides the refinement of M7C3 carbides, the volume fraction of M 7 C 3 carbide also decreases with Ti addition, as shown in Fig.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our previous study by Liu, et al, 1) and other studies by Zhi, et al, 2) Chung, et al 3) and Bedolla-Jacuinde, et al 4) have reported the experimental results on Fe-4wt%C-17wt%Cr, Fe-4wt%C-20wt%Cr, Fe-4wt%C-25wt%Cr and Fe-2.5wt%C-16wt%Cr high chromium cast irons with different Ti-additions, as shown in Table 1. They found that, besides the refinement of M7C3 carbides, the volume fraction of M 7 C 3 carbide also decreases with Ti addition, as shown in Fig.…”
Section: Introductionmentioning
confidence: 93%
“…4 in our previous work [1]), it is clarified that the eutectic transformation in multicomponent alloy system is different from that in binary alloy system. That is, in multicomponent alloy system, the eutectic transformation does occur within a temperature range but not under a constant temperature.…”
Section: Phase Precipitation Sequencementioning
confidence: 99%
See 3 more Smart Citations